Desenvolvimento e validação de vídeo educativo para famílias de pessoas com colostomia por câncer - Rosa, Bruna Vanessa Costa da (2015)
The diagnosis of a cancer occurs within a family context and, to a greater or lesser extent, affects family members and triggers changes in its functioning. In the case of colon and rectal cancer, the challenge may be greater due to the need to perform a colostomy. In this context, the form of nursing practice becomes important for the development of actions aimed at improving the quality of life for both the person with the colostomy as for the family. In this sense, interventions through educational technologies aim to strengthen the family and make allowances for them to develop coping strategies, social and family life and the care strategies that more closely resemble the family operation. Thus, the study aimed to develop and validate an educational video for families of people with a colostomy by cancer. It is a methodological research study, whose setting was the city of Santa Maria, Rio Grande do Sul, Brazil. The development and validation of the video occurred between april and october 2014, after approval by the Ethics Committee of the Federal University of Santa Maria, with CAAE number 28062514.8.0000.5346. Study participants were seven experts-judges and the target audience was represented by two families with a carrier of colostomy by cancer. The study was conducted in four stages: construction of the script, script validation (instrument type Likert Scale), educational video development and validation of the video. With the script validation, was developed the video, which lasted 8 minutes and 35 seconds. The video validation occurred through interviews and filling out an assessment tool. Given the answers to the blocks of each of the evaluation items of the validation instrument, quantitative analysis was performed according to the corresponding valuations, as well as analysis of behavioral representation. The data collected in the video validation phase, through interviews, were analyzed using the proposed of qualitative analysis of Polit. In the results,was perceived a tendency by the agreement between the responses of experts-judges and target audience to validation tools, obtaining a positive assessment. Thus, it could be deduced that there was no significant indication of disagreement between the participants. Considering that these families live a moment of doubt and uncertainty, mainly related to the future, it is considered that the video may contribute significantly so that they can better understand what they are living and reflect about what can help them in this new walk, as well as developing skills and autonomy in the new reality.